The role of GO-NGO-PO collaboration and the local government units in sustainable crop and livestock industries (SCLI) the case of banana industry in Mapatag, Hamtic, Antique (1998-2003) - Dava, Leila S. (2002.)
This study has the following objectives: (1) To identify the agricultural constraints and problems of the farmers in Barangay Mapatag, hamtic Antique; (2) To find out the nature and purpose of the SCLI project (namely the establishment of the Banana Industry) in relation to the overall SCLI constraints and problems of the community (30 To determine the role of the NGO-PO-GO collaboration in the SCLI project; (4) to know the role of local government units in the area in relation to the conduct of the SCLI project and; (5) To find out the initial outcome of the NGO-PO-GO collaborative project., The research include interviews, participant observation, group discussion and an examination of published and unpublished materials. The site of the research is the agricultural community in Barangay Mapatag in Hamtic Antique. The respondents are composed of the officers and members of the various agencies involved in the projects as well as the beneficiaries or the farmers. The research concludes that community or grassroots participation is essential in any development thrust of the government. The research further establishes that given adequate financial, technical and infrastructure support from the concerned government and nongovernment organizations, rural farmers can manage their own resources in sustainable ways.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Sustainable Crop and Livestock Industries; Banana Industry